If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2n = -8 + 3(-4n + -2) Reorder the terms: 6 + -2n = -8 + 3(-2 + -4n) 6 + -2n = -8 + (-2 * 3 + -4n * 3) 6 + -2n = -8 + (-6 + -12n) Combine like terms: -8 + -6 = -14 6 + -2n = -14 + -12n Solving 6 + -2n = -14 + -12n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '12n' to each side of the equation. 6 + -2n + 12n = -14 + -12n + 12n Combine like terms: -2n + 12n = 10n 6 + 10n = -14 + -12n + 12n Combine like terms: -12n + 12n = 0 6 + 10n = -14 + 0 6 + 10n = -14 Add '-6' to each side of the equation. 6 + -6 + 10n = -14 + -6 Combine like terms: 6 + -6 = 0 0 + 10n = -14 + -6 10n = -14 + -6 Combine like terms: -14 + -6 = -20 10n = -20 Divide each side by '10'. n = -2 Simplifying n = -2
| 1-3y/5-4=2y/3 | | 4(3x-5)-12(x-5)=70 | | 1+3x=4+4x | | (2x-7)y=15 | | x=x-u | | -10-9k=-91 | | -8x-3x-11=-8x+7 | | 3x-10(x+2)=sqrt(13)-7x | | -8x-3x-11=-8+7 | | 99=5n+9 | | 4(3x-5)+12(x-5)=70 | | 6-6(5+5m)=-24+8m | | X^2+5x+7=49 | | X^2+5x+58=0 | | R^3-r^2-4r+4=0 | | log(6x+8)=log(12) | | -7(8k-8)=-392 | | 720/6 | | 3cos^2x=2 | | 6tons=Pounds | | 720/3 | | Y=-1/2(x-6)(x8) | | 2(3x+2)=4(2x-5) | | 8s-26+5s-15=180 | | 6b+4b=-12+8b | | 25*7+11*3+2*3= | | 2x^2+-8x-384=0 | | 2(x+2)=-2(x+6) | | 44=x(5+6) | | 7x-(2x+5)=36 | | 2w-36=w-12 | | 46*7+87*3+21*3= |